Physiological Changes Across Historical Sorghum Hybrids Released During the Last Six Decades - P. A. Demarco; L. Mayor; S. Tamagno; J. A. Fernandez; P. V. Vara Prasad; J. L. Rotundo; C. D. Messina; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2020)
For the last decades, sorghum (Sorghum bicolorL. Moench) improvement in the United States (US) has been related to targeted modifications in genotype, environment, and management (G × E × M) combinations. Retrospective studies are relevant to document changes in the phenotype associated to breeding process and to explore alternatives to improve yield and its physiological associated traits. This study aims to characterize yield changes over time for hybrids with different year of release. Field trials were conducted during 2018 and 2019 growing seasons in eight environments/site-years across the states of Kansas and Texas including 20 grain sorghum hybrids released between 1963 and 2017. Grain yield was measured across all hybrids and environments. Detailed physiological descriptors were measured in one of the environments including grain filling, grain set efficiency (grains g-1) at flowering, panicle length, and dynamics of water-soluble carbohydrates (WSC) during the reproductive period. Overall sorghum grain yield improvement was 0.4 bu/a/year (P<0.005). Grain set per unit of reproductive biomass at flowering was positively associated with the hybrid’s year of release, explaining the increases in grain number. Panicle size increased in newer hybrids, thus, supporting the reported changes in grain number per unit area. Modern sorghum hybrids displayed greater WSC remobilization during the reproductive period (P<0.05). However, further research on sorghum’s WSC dynamics is needed for understanding its contribution to yield improvement.
Keywords: sorghum hybrids; yield gain; yield components; water soluble carbohydrates; (WSC)